First-principle computations of ferromagnetic HgCr2Z4 (Z = S, Se) spinels for spintronic and energy storage system applications - Charlie Dunnill (Journal of Materials Research and Technology, 2020)
We explored electronic spin-dependent physical aspects of ferromagnetic HgCr2Z4 (Z = S, Se) spinels using density functional theory (DFT) for spintronic and energy storage applications. In calculations of structural, electronic, magnetic, and transport aspects, we used Perdew-Burke-Ernzerhof generalized gradient approximation (PBEsol GGA) plus modified Becke-Johnson (mBJ) potential. To calculate structural parameters, we optimized both spinels in the ferromagnetic phase and our predicted data of structural parameters show good comparison with existing experimental data. Also, the calculated negative formation energy confirms the structural stability of the studied spinels. Analyzingferromagnetic nature of studied spinels based on exchange splitting energy and magnetic parameters, we used mBJ potential to calculate band structure (BS) and density of states (DOS). By exploring DOS, we found the dominant role of electrons spin has been shown by negative indirect exchange energy Δx(pd) values and the fulfillment of the condition Δx(d) >ΔEcry. In addition, exchange constants (N0α and N0β) and magnetic moments were also calculated to ensure their ferromagnetism in studied spinels. Further, the exploration for the influence of electrons spin on electronic transport aspects has been done by investigating electrical and thermal conductivities, Seebeck coefficient, and power factor by using classical Boltzmann transport theory.